Employee Stock Option Exercise and Firm Cost - CARPENTER, JENNIFER N.; STANTON, RICHARD; WALLACE, NANCY (Journal of Finance, 2019)
ABSTRACT We develop an empirical model of employee stock option exercise that is suitable for valuation and allows for behavioral channels. We estimate exercise rates as functions of option, stock, and employee characteristics using all employee exercises at 88 public firms, 27 of them in the S&P 500. Increasing vesting frequency from annual to monthly reduces option value by 11% to 16%. Men exercise faster, reducing value by 2% to 4%, while top employees exercise slower, increasing value by 2% to 7%. Finally, we develop an analytic valuation approximation that is more accurate than methods used in practice.